Desindustrialização ou reestruturação industrial no Brasil: as reformas estruturais e a "doença holandesa" - Wasques, Renato Nataniel (2012)
In the period 1990-2010 the discussion about the process of de-industrialization of the Brazilian economy has intensified. This discussion generated a different set of arguments. These differences relate to the presence (or not) of the process of de-industrialization in the Brazil. In this sense, this dissertation aims at investigating the occurrence (or not) the phenomenon of de-industrialization in the Brazilian economy in the period 1990-2010. For this, the analysis has taken as starting point the following problems: The changes in the Brazilian manufacturing industry during the 1990s shaped a process of de-industrialization, or, conversely, a marked process of industrial restructuring? The Brazilian economy has been contaminated by the "Dutch disease" throughout the 2000s? This "disease" would be triggering a process of premature de-industrialization? The working hypothesis is that changes in the Brazilian manufacturing industry in the 1990s shaped a process of industrial restructuring. Moreover, it is considered that the Brazilian economy had not been contaminated by the "Dutch disease" throughout the 2000s because not there was a generalized process of reprimarization the Brazilian export basket. This research was conducted through the systematic analysis of secondary data, which include bibliographical and documentary research on the subject, complementing the study of journals, interviews and publications of authors who work the subject. Resorted to the database available on the website of IPEADATA, FUNCEXDATA, the data provided by IBGE, BACEN and MDIC. These survey results reinforce the hypothesis that changes in the Brazilian manufacturing industry in the 1990s shaped a process of industrial restructuring. Furthermore, this research identified several symptoms of the phenomenon of "Dutch disease" in the Brazilian economy in the period 2000-2010. The question that the phenomenon of "Dutch disease" would be triggering a process of premature de-industrialization in the Brazilian economy, the responses obtained were controversial. Finally, the analyzes indicate a tendency toward regressive specialization of Brazilian industrial structure.